Host range in economically important fruit trees associated with foliar phytopathogens of peach (Prunus persica l). (Bioagro, 2023)
In Mexico, the presence of phytopathogenic fungi causes severe damage to peach (Prunus persica L.) fruits after harvest, causing a decrease in the export of processed products and in shelf life. The objective of this work was to describe the host range of foliar fungi in fruits of apple (Malus domestica Borkh), strawberry (Fragaria spp.), plum (Prunus domestica L.), pear (Pyrus communis L.) and quince (Cydonia oblonga Mill.) and on leaves of peach varieties. For the pathogenicity test, the spray technique was used and the diseases were assessed using the 5-degree severity scale from 0 to ≥75% of presence of symptoms on the fruit and from 10 to ≥60% for detached leaf and percentage of incidence. Conidia of Fusarium spp, Alternaria spp, Epicoccum spp, Collectotrichum spp and Monilinia spp. were inoculated from all the fruits and leaves of the yellow, prisco and white peach varieties, with seven replicates, leaving a control with sterile distilled water for each treatment. They were placed in a humid chamber under aseptic conditions, at 27°C ± 1, and were subjected to regimes of 14 hours of darkness and 10 hours of light for 4, 7, 10 and 12 days. Data were subjected to analysis of variance and Tukey's test for comparison of means (P≤0.05). The yellow variety of peach presented greater susceptibility to all fungi, which were pathogenic to the hosts with severity from 0 to 97.14 %.
Keywords: fruit; fungi; inoculate; pathogenicity; severity